2022
DOI: 10.1007/s00431-022-04388-w
|View full text |Cite
|
Sign up to set email alerts
|

Potentially effective drugs for the treatment of COVID-19 or MIS-C in children: a systematic review

Abstract: The purpose of this systematic review is to evaluate the efficacy and safety of using potential drugs: remdesivir and glucocorticoid in treating children and adolescents with COVID-19 and intravenous immunoglobulin (IVIG) in treating MIS-C. We searched seven databases, three preprint platform, ClinicalTrials.gov, and Google from December 1, 2019, to August 5, 2021, to collect evidence of remdesivir, glucocorticoid, and IVIG which were used in children and adolescents with COVID-19 or MIS-C. A total of nine coh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 48 publications
0
31
0
2
Order By: Relevance
“…Although multiple treatments have been evaluated since the beginning of the COVID-19 pandemic: chloroquine or hydroxychloroquine, azithromycin, ivermectin, lopinavir/ritonavir, convalescent plasma, intravenous immunoglobulin, and interleukin (IL)-6 inhibitors, none of them have proven efficacy and safety in the pediatric population. However, despite the evidence in pediatric patients being insignificant and of low quality ( 3 , 4 ), some guidelines recommend the use of remdesivir in critically ill patients ( 2 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although multiple treatments have been evaluated since the beginning of the COVID-19 pandemic: chloroquine or hydroxychloroquine, azithromycin, ivermectin, lopinavir/ritonavir, convalescent plasma, intravenous immunoglobulin, and interleukin (IL)-6 inhibitors, none of them have proven efficacy and safety in the pediatric population. However, despite the evidence in pediatric patients being insignificant and of low quality ( 3 , 4 ), some guidelines recommend the use of remdesivir in critically ill patients ( 2 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our systematic review identified three single-arm cohort studies with 112 children and adolescents with COVID-19, with data collected between January 2020 and August 2021 [ 30 ]. In one of these studies, all patients had severe COVID-19 [ 37 ]; in another study, 75% of the patients were admitted to the pediatric intensive care unit (PICU) [ 38 ]; and in the third study, 22% of the patients received mechanical ventilation [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our systematic review, which included one prospective cohort study and one case series with a total of 69 children and adolescents with COVID-19, with data collected between January 2020 and August 2021, did not find statistically significant impact of glucocorticoid therapy on the critical outcomes mortality (OR 2.79, 95% CI: 0.13 to 60.87), mechanical ventilation (OR 2.83, 95% CI: 0.78 to 10.30), or duration of PICU admission (weighted mean differences [WMD] 2.0, 95% CI: − 0.95 to 4.95) when compared with no glucocorticoid therapy [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations